2019
DOI: 10.1016/j.ypmed.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Cervical and colorectal cancer screening prevalence before and after Affordable Care Act Medicaid expansion

Abstract: Community health centers (CHCs), which serve socioeconomically disadvantaged patients, experienced an increase in insured visits after the 2014 Affordable Care Act (ACA) coverage options began. Yet, little is known about how cancer screening rates changed post-ACA. Therefore, this study assessed changes in the prevalence of cervical and colorectal cancer screening from pre- to post-ACA in expansion and non-expansion states among patients seen in CHCs. Electronic health record data on 624,601 non-pregnant patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…(Blood pressure screening did not increase after ACA implementation among Medicaid nonexpansion states but was already very high before the ACA and remained high in both expansion and nonexpansion groups.) These findings are consistent with previous literature that suggests other preventive services like mammography and colorectal cancer screening increased overall after the implementation of the ACA (Alharbi et al, 2019;Huguet et al, 2019;Sun et al, 2018). Gains in preventive service delivery have previously been attributed to broad insurance expansion (both public and private) (Huguet et al, 2017), development of Accountable Care Organizations with incentivized focus on quality metrics (although the proliferation of Accountable Care Organizations was underway before Medicaid expansion in 2014) (Meyer et al, 2017), and additional resources for safety net health centers through federal grants and increased health insurance revenue (Han et al, 2017;Huguet et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…(Blood pressure screening did not increase after ACA implementation among Medicaid nonexpansion states but was already very high before the ACA and remained high in both expansion and nonexpansion groups.) These findings are consistent with previous literature that suggests other preventive services like mammography and colorectal cancer screening increased overall after the implementation of the ACA (Alharbi et al, 2019;Huguet et al, 2019;Sun et al, 2018). Gains in preventive service delivery have previously been attributed to broad insurance expansion (both public and private) (Huguet et al, 2017), development of Accountable Care Organizations with incentivized focus on quality metrics (although the proliferation of Accountable Care Organizations was underway before Medicaid expansion in 2014) (Meyer et al, 2017), and additional resources for safety net health centers through federal grants and increased health insurance revenue (Han et al, 2017;Huguet et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Overall, receipt of preventive services among female CHC patients remained low despite broad improvements that were observed after implementation of the ACA and were present among both Medicaid expansion and nonexpansion states. Still, with the exception of the rate of flu vaccination in nonexpansion states (see the Limitations section), the observed prevalence of receipt of individual preventive services was roughly similar to other studies measuring preventive care in this population (Cowburn et al, 2013;Huguet et al, 2019;Walker et al, 2018), although they lag far behind aspirational metrics such as Healthy People 2020 (Office of Disease Prevention and Health Promotion, 2014). Reasons for a lack of consistent differences in pre-/post-ACA implementation delivery of services between Medicaid expansion and nonexpansion states are likely multifactorial and require further exploration in additional states and with additional types of services.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Medicaid expansion has improved access to care among low-income individuals (49,50). More specifically, studies have found Medicaid expansion was associated with increased cancer screenings among low-income adults (51)(52)(53)(54). Illinois is one of the states with early implementation of Medicaid expansion (55).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these tools usually detect only one cancer type, meaning that individuals may need to visit multiple medical services to receive different screening tests. These disadvantages lead to low compliance with cancer screening by these tools [ 8 ].…”
Section: Introductionmentioning
confidence: 99%